2016
DOI: 10.1111/micc.12289
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Zebrafish to Identify Anti‐(Lymph)Angiogenic Compounds for Cancer Treatment: Promise and Future Challenges

Abstract: Cancer metastasis which predominantly occurs through blood and lymphatic vessels, is the leading cause of death in cancer patients. Consequently, several anti-angiogenic agents have been approved as therapeutic agents for human cancers such as metastatic renal cell carcinoma. Also, anti-lymphangiogenic drugs such as monoclonal antibodies VGX-100 and IMC-3C5 have undergone phase I clinical trials for advanced and metastatic solid tumors. Although anti-tumor-associated angiogenesis has proven to be a promising t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 175 publications
(208 reference statements)
0
15
0
Order By: Relevance
“…The blood vessels that grow into the xenograft have been shown to form an abnormal network of varying vessel morphology typical of mammalian tumours (Zhao et al, 2011a). The xenograft can be imaged in vivo , allowing observation of the mechanisms driving tumour vascularisation, such as sprouting angiogenesis, vascular co-option and endothelial cell migration (Zhao et al, 2011a,b), and can be used to screen for novel anti-angiogenesis drugs (Okuda et al, 2016). Despite the successes of this model, the precise role of the xenografted tumour cells and tumour-associated immune cells, with respect to the stimulation of angiogenesis, has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…The blood vessels that grow into the xenograft have been shown to form an abnormal network of varying vessel morphology typical of mammalian tumours (Zhao et al, 2011a). The xenograft can be imaged in vivo , allowing observation of the mechanisms driving tumour vascularisation, such as sprouting angiogenesis, vascular co-option and endothelial cell migration (Zhao et al, 2011a,b), and can be used to screen for novel anti-angiogenesis drugs (Okuda et al, 2016). Despite the successes of this model, the precise role of the xenografted tumour cells and tumour-associated immune cells, with respect to the stimulation of angiogenesis, has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…These cells migrated ventrally to the dorsal aorta to form the thoracic duct, which previously had only been hypothesized and indirectly supported but not directly measured[58]. Other transgenic zebrafish lines with fluorescent vasculature are reviewed extensively by Okuda et al[57]. …”
Section: Lymphatic Imaging Using Transgenic Fluorescent Reporter Micementioning
confidence: 99%
“…Taking advantage of the optical clarity of zebrafish embryos, investigators have been able to observe a wide range of vascular phenomena, including sprouting, remodeling, endothelial proliferation, and lumen formation, which are more difficult to study in the opaque embryos of mice. In addition, many new anti-lymphangiogenic compounds have been discovered using this model[57]. Zebrafish are especially useful for live imaging of deep lymphatic structures, such as the thoracic duct.…”
Section: Lymphatic Imaging Using Transgenic Fluorescent Reporter Micementioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have found that CP-7 presents the characteristics of low toxicity, high selectivity against VEGFR3, and potent inhibitory effect on VEGFR3-positive cancer cells both in vitro and in vivo. Practically, IMC-3C5 (NCT01288989), an anti-VEGFR3 antibody, has shown anti-BC activity in clinical practice. , To date, no VEGFR3-selective small-molecule inhibitor has been authorized by the FDA. It is necessary to identify a highly selective VEGFR3 inhibitor for the treatment of BC.…”
Section: Introductionmentioning
confidence: 99%